Airway and vascular access - Luedtke, Glenn H.; MosbyJems (Firm) (St. Louis : MosbyJems, 2003)
Discusses airway anatomy, oxygen delivery systems, alternatives for airway management, including indications and contraindications (airway adjuncts, endotracheal intubation, alternatives), suctioning, ventilation techniques, and methods and alternatives for vascular access (intravascular access, intraosseous access)
Presenter, Glenn Luedtke
VHS
Keywords: Airway Obstruction -- therapy; Emergency Treatment